Development of the information subsystem for monitoring pollution of natural healing resources caused by road transport - Мещеряков, Владимир Иванович; Гнатовская, Анна Арнольдовна; Черепанова, Екатерина Валерьевна; Фоменко, Виталий Викторович (Eastern-European Journal of Enterprise Technologies, 2014)
Natural healing resources (mud, mineral water, etc.) are affected by man-made pollution, such as road transport, therefore, require monitoring of their condition and taking protective measures to mitigate these impacts. Implementation of the task is impossible without creating an information system for monitoring and subsequent analysis of the impact of polluting factors on changes in biochemical composition of healing resources. Concerning necessary functions, this information tool should provide storage of information about the biochemical properties of natural healing resources, identify the composition and concentrations of pollutants from a particular source, reveal the pattern of pollutants distribution in the atmosphere. Based on the analysis, it is shown that the function of the storage of data about characteristics of natural healing resources with reference to the map is advisable to implement in the form of cadastre, built using web-technologies, with the ability to work both in local and on-line modes. This reduces the subsystem cost and allows operation both in stationary and field conditions using standard methods. As a subsystem of motor vehicle pollutant transformation in composition and concentration of impurities in the atmosphere, European calculation method COPERT 4 and software based on it was used, which has allowed to agree the parameters of pollutants with international standards and compare results. Subsystem for modeling the pollutants distribution in the atmosphere and its software implementation, based on a bimodal Gaussian model, which takes into account the pollution source reflection from the surface, resulting in a so-called "mirror" pollution source, as well as wind vector was developed. The correctness of the model is confirmed by external experimental studies that allows to predict the impurities distribution on the area of natural healing resources distribution, depending on weather conditions.